Routledge international handbook of poverty - Greve, Bent (Routledge international handbooks., 2020)
"The first of the UN Millennium Goals was to reduce extreme poverty and it was in 2014 halved compared to 1990, and now the goal is to eradicate poverty and hunger by 2030. The reduction in poverty is to a high degree the consequence of the rapid economic development in a few countries, especially China, but in many countries around the globe poverty is still high and influencing societies' overall development. It is against this background that this Handbook provides an up to date analysis and overview of the topic from a large variety of theoretical and methodological angles. Organized into four sections, the Handbook provides knowledge on what poverty is, how it has developed, and what type of policies might be able to succeed in reducing poverty. The first section investigates conceptual issues and relates concepts to people's relative position in society and the understanding of justice. The second section shows how poverty has developed. It will combine existing empirical knowledge with regional/national understanding of the issue of poverty. The third section analyses policies and interventions with the aim of reducing or alleviating poverty within a national as well as global context. It will and intends to include a variety of countries and examples. The last section tells us what can be done about poverty, what instruments are available to end poverty as we know it today. This volume will be an invaluable reference book for students and scholars throughout the social sciences, particularly in sociology, social policy, public policy, development studies, international relations and politics"--